2019
DOI: 10.1002/jmv.25611
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of VAIN, CIN, and related HPV genotypes in Japanese women with abnormal cytology

Abstract: Vaginal intraepithelial neoplasia (VAIN) is often found by chance. We investigated the prevalence of VAIN and related human papillomavirus (HPV) types in comparison with cervical intraepithelial neoplasia (CIN). This study enrolled 648 women who were referred to the outpatient clinic determined using Genosearch-31 + 4, which can detect 35 different HPV types.Colposcopy was performed at the first visit by an experienced gynecological oncologist. Among 611 subjects with squamous cell lesions, 107 (17.5%) VAIN ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 31 publications
4
22
1
Order By: Relevance
“…Another report showed that 93.6% of vaginal intraepithelial lesions (VaINs) are positive for HPV [15]. We have also reported that various HPV types are identified in the vaginal lesions, and HPV is positive in 84% of VaIN1 cases and 100% of VaIN2/3 cases [16]. Highly sensitive HPV testing has shown that most VaIN cases are positive for HPV, although a few cases of VaIN1 have been shown to be negative for HPV [13,16].…”
Section: Introductionmentioning
confidence: 81%
See 2 more Smart Citations
“…Another report showed that 93.6% of vaginal intraepithelial lesions (VaINs) are positive for HPV [15]. We have also reported that various HPV types are identified in the vaginal lesions, and HPV is positive in 84% of VaIN1 cases and 100% of VaIN2/3 cases [16]. Highly sensitive HPV testing has shown that most VaIN cases are positive for HPV, although a few cases of VaIN1 have been shown to be negative for HPV [13,16].…”
Section: Introductionmentioning
confidence: 81%
“…We have also reported that various HPV types are identified in the vaginal lesions, and HPV is positive in 84% of VaIN1 cases and 100% of VaIN2/3 cases [16]. Highly sensitive HPV testing has shown that most VaIN cases are positive for HPV, although a few cases of VaIN1 have been shown to be negative for HPV [13,16]. During the carcinogenic process after HPV infection, in addition to the HPV genotype, the infection site may also be important.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…HPV18 was rare in Asian patients with VAIN [ 25 ]. A Japanese study reported HPV52, 16, 51, 53 and 56 were the most common types in patients with VAIN [ 26 ]. However, an Italian study [ 5 ] reported that the top four common HPV genotypes associated with multicentric lesions were HPV16, HPV18, HPV33 and HPV31.…”
Section: Discussionmentioning
confidence: 99%
“…In Japan, Genosearch-31 (GS-31) (MBL, Nagoya, Japan), a high-resolution PCR-SSOP-Luminex-based method that combines PCR and a sequence-specific oligonucleotide probe (SSOP) with a Luminex xMAP system has been used to discriminate 31 HPV genotypes in various studies [ 51 , 171 , 172 ]. Japanese research teams have also collaborated with Mongolia, Cambodia, and Laos in HPV epidemiological studies.…”
Section: Hpv Screeningmentioning
confidence: 99%